Guest Editorial Special Section From the Selected Extended Papers Presented at the CAD-TFT 2020 - Samar K. Saha; Arokia Nathan; Xiaojun Guo; Sanjiv Sambandan (IEEE Journal of the Electron Devices Society, 2021)
This Special Section follows from a selection of highly-rated, high impact technical papers presented at the 11th International Conference on Computer-Aided Design for Thin Film Transistor Technologies (CAD-TFT) 2020. The CAD-TFT 2020 was held as a virtual conference on November 10th and 11th, 2020 from the operations center at Tianjin, China. The pre-conference virtual presentations on November 9th, 2020 included six tutorials from internationally recognized experts in their technical fields as well as six posters from China, India, and Canada.